STRATEGI PEMERINTAHAN KAMPUNG DAYUN DALAM PENGELOLAAN POTENSI WISATA TAHUN 2022 - Rani, Rahma; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The government's strategy in managing the potential in the village is one of the important aspects in tourism development, namely the strategy carried out by the village government because the government's success in developing tourism potential is very dependent on the ability of the bureaucracy or government organization in managing its tourism resources. The aim of this research is to find out what the Dayun Village government's strategy is in managing tourism potential in 2022. This research was conducted in the Dayun tourist village or better known as Dayun Village. This research uses a qualitative approach with descriptive methods. In collecting data the author used interview and documentation techniques. This research uses the theory put forward by Fred.R. David, namely Strategy Formulation, Strategy Implementation, and Strategy Assessment/Evaluation. The results of this research concluded that the management of tourism potential in the village is not yet fully optimal, but the management of tourism potential by the Dayun village government is handed over to Pokdarwis Dayun but it is still under the supervision of the Dayun village government and does not reduce the involvement of the village government in its management. The Dayun Village Government's strategy in managing tourism potential is the formulation and implementation of policies, optimizing tourism promotion, strengthening institutions, conducting comparative studies to other tourist villages, facilitating and evaluating strategies. Keywords: Village Government Strategy, Tourism Potential Management